BERMAIN PUZZLE MEMUPUK SIKAP KEMANDIRIAN PADA ANAK USIA DINI - Ni Ketut Alit Suarti (Jurnal Paedagogy, 2015)
Early childhood is a child aged 0-6 years who is undergoing a process of rapid development and is fundamental to the next life. For early childhood, play is a world to get pleasure and through play it can accumulate all aspects of child development, be it cognitive, physical motor, social emotional, language, and moral values. In playing children using media, one of them is puzzle media, so it is called puzzle playing. Playing puzzles is a fun activity that is done voluntarily using pieces of pictures that are strung together to form a particular shape or picture. The benefits of playing puzzles are training children to solve problems, develop eye and hand coordination, develop children's motor skills, develop cognitive skills, train patience, train children to explore, and train children to be independent not dependent on friends. In playing puzzles, children must be disciplined in placing pieces of pictures or shapes and commit to placing them in the right place. Basic discipline and commitment to form an attitude of independence. Independence is a state of attitude that a person can stand alone without depending on others. Children who have an independent attitude can be seen from children being able to think critically, creatively and innovatively, not easily influenced by other people's opinions, not running away or avoiding a problem, able to solve problems by thinking deeply, not feeling inferior, trying to work with is full of diligence and discipline, and is responsible for his actions. Children who are successful in playing puzzles will tend to want to try or repeat with other shapes even using more difficult pieces, and so on and unconsciously the child plays with an independent attitude, meaning that the child doesn't want to be helped to finish the game. An attitude of independence needs to be nurtured from an early age in order to prepare reliable human resources in the future to achieve a happy, prosperous and prosperous society.